Pengaruh penerapan model pembelajaran inkuiri tipe pictorial riddle berbantuan media pembelajaran interaktif terhadap pencapaian kompetensi IPA siswa kelas VIII SMPN 31 Padang - Dessy Ratnasari; Yurnetti Yurnetti; Hidayati Hidayati; Syafriani Syafriani (Universitas Negeri Padang, 2020)
Education is an effort to provide certain knowledge, insights, skills and expertise to individuals to develop their talents and abilities. Science (IPA) is a branch of science that has an important role in the education process, because it requires students to think and have a scientific attitude that organized and systematic. But the achievement of learning outcomes in science subjects that are not optimal because students are less involved in getting the concept of learning science. Besides that the use of models used in learning is still not diverse and has not used the media fully. Therefore, researchers use the Inquiry learning model pictorial riddle type assisted by interactive learning media as an alternative in overcoming students' boredom in PBM. This study aims to determine the effect of the use of Inquiry learning model Pictorial Riddle Type Assisted by Inactive Media on the Achievement of Competencies of Grade 8 Students of SMP N 31 Padang. The kind of this research is a quasi-experimental research design with a randomized control group pretest-posttest design. The study population was all classes VIII 1 - VIII 5 taught by the same teacher with the same number of hours at SMP N 31 Padang registered in 2019/2020. The sampling technique that used in this research is purposive sampling. The research data used are student learning outcomes data for knowledge competence. The research instrument used was a written test to measure knowledge competence. The research data were analyzed by two average similarity tests. The results showed the average value of science learning outcomes for knowledge competence in the experimental class 72.41 and the control class 65.98. The conclusion of the research is the hypothesis which states that there is a significant influence of the use of the Inquiry learning model of pictorial riddle type assisted by interactive learning media on the achievement of science competencies of grade 8 students of SMP N 31 Padang..